Reseña de Casas Gómez, M. (dir.), Paredes Duarte, Mª J. y Varo Varo, C. (eds.) (2005). VIII Jornadas de Linguística. - Carmen Varo Varo; M. Jesús Paredes Duarte (Pragmalingüística)
Se trata de una reseña de Casas Gómez, M. (dir.), Paredes Duarte, Mª J. y Varo Varo, C. (eds.) (2005). VIII Jornadas de Linguística.